Aviation maintenance in multicultural settings : the challenges of cultural tolerance and of employees' maintenance resource management/human factors (MRM/HF) awareness - Al-Harabi, Ali (Cranfield University, 2001)
This thesis deals with two major issues, the first is the multicultural nature of many Aircraft Maintenance Technicians (AMTs) teams and the way in which cross-cultural communication and/or barriers to communication might affect teams' performance; and the second is the practice of Maintenance Resource Management/Human Factors (MRM/HF) in developing countries. Using the questionnaire method, this research examines the opinions of AMTs and maintenance supervisors from eight maintenance organisations regarding their attitudes to colleagues from other nations and cultures, and how this might affect their performance in the workplace. It also seeks to probe the respondents' attitudes to, for example, stress, responsibility, attitude to authority and handling conflict, considering these opinions alongside the national and cultural backgrounds of the participants. In order to do this, the respondents themselves were organised into different "culture groups" with the national characteristics of the groups being defined according to Hofstede's ideas of individualistic and collectivistic societies. The thesis begins from the premise that most AMTs demonstrate greater individualistic tendencies than airline pilots, and while their individualism may be partly traceable to the signatory authority of A&P, other factors, such as education, training and working/ socialising with Westerners, are also important influences. This study aims to show that a large contingent of AMTs and maintenance supervisors from collectivistic cultures share many of the attitudes and work goals of individualists. For example, this study will show that AMTs and maintenance supervisors from most collectivistic cultures lean towards a preference for a command style that is closer to the egalitarian pole than to the hierarchical one; tend to reject the idea of blind obedience to supervisors; tend to believe that technical merit, not social status or good connections, makes for successful managers; lean towards the acceptance of only a modicum of rules to deal with the issue of uncertainty in the workplace; tend to favour work goals that pertain to their personal needs and career aspirations, etc. The study also sheds light on AMTs and maintenance supervisors' belief systems, inter-ethnic stereotypes and feuds in the workplace, and on that basis, constructs profiles of the eight aviation maintenance organisations previously mentioned. This also addresses the question of whether these companies have met the cultural diversity and MRMawareness challenges. The analysis specifically provides answers to the fundamental questions of this study, such as whether AMTs and maintenance supervisors from some collectivistic cultural groups do, in fact, have attitudes and work goals that are similar to those of AMTs and maintenance supervisors from individualistic cultural groups; whether ANITs, as a professional group, are actually more individualistic than are airline pilots from the same countries in attitudes and work goals; to what extent ANITs' work-related attitudes and values are universal, or are influenced by their national cultures; whether placing AMTs from different national cultures in the same work teams has deleterious effects on the functioning of an aviation organisation; whether multicultural teams face insurmountable problems as functioning units because of stereotypes, discrimination, and other ills; whether the management of aviation maintenance organisations has been meeting the challenges of cultural diversity effectively, i. e. whether management has minimised cultural diversity as a potential performance barrier, and has, instead, begun to mine value-added potential of cultural diversity; and whether aviation maintenance organisations have met the NIRM-awareness challenge.